From software architecture descriptions to object-oriented designs - Rodríguez, Guillermo Horacio (2014)
Service-Oriented Architecture (SOA) is becoming a dominant approach for developing distributed enterprise-wide applications. One of the reasons for SOA’s extended use is its capacity to rapidly build applications by assembling alreadyimplemented and Internet-accessible services, which allows software organizations to hasten development of distributed applications and their consequent time-tomarket. However, this approach to develop SOA applications results unsuitable for particular organizations with high-priority and critical demands of internal control, security, flexibility, confidentiality and data integrity of their services, since the development of core functionality may be jeopardized by either uncertainty or changing environment. Although many efforts have focused mainly on facilitating discovering of services, and the outsourcing and reuse of them in SOA-based applications, little attention has been paid to aiding designers in developing services associated with business goals and quality-attribute properties. Moreover, quality-attribute properties of the service assemblies have been disregarded, which often leads to mismatches between the quality-attribute behavior prescribed by the SOA and the one resulting after its implementation. (Párrafo extraído del texto a modo de resumen)